EVALUASI PENERAPAN JSA DAN HIRADC PENGGUNAAN TOWER CRANE PADA PROYEK JALAN TOL CINERE-JAGORAWI SEKSI 3 PT PP PRESISI TBK TAHUN 2022 - Calviano Ramadhani Prakoso (2022)
JSA and HIRADC are some of many tools used for identification, analysis, and determining control of hazard risk at workplace that belonged to a risk control hierarchy, administration control. JSA and HIRADC could be implemented on construction sites, for example at tower crane operation at toll road project Cinere-Jagorawi section 3 by PT PP Presisi Tbk for hazard risk control. This research was purposed to evaluate the implementation of hazard risk control using JSA and HIRADC to rise the standard of hazard risk control of operating tower crane by PT PP Presisi Tbk in 2022. This research is using a design study qualitative by observation to check the suitability of implementation and interviews with informants chosen by purposive sampling technique. The result of this research shows the suitable of implementation of controlling hazard risk from operating a tower crane is excellent and ideal with JSA and HIRADC. Even so, there is still a hazard that hasn't been wrIted in JSA and HIRADC of operating tower crane at toll road project Cinere-Jagorawi section 3. Advice for the company, there must be an update for the document of JSA and HIRADC of operating tower crane by PT PP Presisi Tbk.